Development of Learning Modules Using the Dick and Carey Model in Informatics Subject - Suzatmika, Iwan Hadi; Rohman, Ujang; Prayogo, Prayogo (EDUCATIO : Journal of Education, 2023)
This study aims to produce learning modules for informatics learning modules for the 10th grade that are appropriate to the Independent Curriculum and make it easier for teachers to present teaching material and make it easier for students to learn. The model which was used in this development was the Dick and Carey development model. The results of this development research are in the form of a learning module for informatics, which is designed systematically, operationally, in a directed manner and completed by some guides for teachers on how to use the language that the speakers easily understand. In the development process to obtain products that are appropriate with the objectives, validation is carried out by material experts, design experts, colleagues, and student responses. The results of validation by material experts obtained a total score of 161 percentage 87% worthy category, design experts obtained a total score of 138 with a percentage of 89% worthy category, while colleagues obtained a total score of 63 percentage 90% very worthy in the category.The test was carried out three times, the first on the individual test obtained an average total score of 34.33 percentage 86% worthy category, the second small group test obtained an average total score of 68 percent 91% very worthy in the category, and the three large group tests obtained average score 69.53 percentage 93% very decent category.Thus, when the product is developed it was concluded that the learning module was very worthy to use in learning Informatics subjects.